Sustainable and Digitized Certification of Palm Oil Production : Its Impact on the Environment in Indonesia - Fauzan Pratama, Angga (Universitas Komputer Indonesia, 2021)
The purpose of this study was to explain sustainable and digitized certification of palm oil production and its impact on the environment in Indonesia. In Indonesia, palm oil producers consist of private plantations as the largest national producers (54%), smallholders (39%), and state-owned plantations (7%). The management of smallholder oil palm still have limitations to accessing technology, production facilities, institutions, and marketing. That is the reason all the palm oil companies need certification to make them standard in facing environtment problems. With the system of digitizing certificate, especially for smallholder companies, it enable to help them transformed the business processes as well as waste treatment.